An examination of Malaysia's structural breaks vis-à-vis Japan and the USA - Md. Wahid Murad; Md. Mahadi Hasan; Muhammad Shoeb-Ur-Rahman; Mahmudul Alam (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This paper primarily examines whether Malaysia has had experienced any structural breaks in comparison with its main two trading partners, namely the USA and Japan in 1970s, 1980s, 1990s and 2000s. It also discusses the implications of such structural breaks to Malaysia's economic globalization at the international level. Using some econometric and statistical tools such as the ADF test, transformed lag equation, Chow Breakpoint test, and CUSUM test, the study reveals that only at 1% level of significance income ratio of Japan and Malaysia has had experienced structural breaks in terms of GDP during the periods 1980s, 1990s, and 2000s. In respect of GNI, the study reveals that only at 5% level of significance their income ratio has had experienced structural breaks during these periods. The study further reveals that income ratio of the USA and Malaysia does not have any structural break both in respect of GNI and GDP.
Keywords: 330; Structural breaks; Income ratio; Economic globalization; Income Convergence; Wirtschaftswachstum; Bruttoinlandsprodukt; Strukturbruch; Schätzung; Malaysia; Vergleich; Japan; USA